Zaibatsu's Role in Development of Japan in the Meiji's Emperor Period of Year 1868-1912 - Rahardi B; Sri Handayani; Sumarjono Sumarjono (History Education, University of Jember, 2018)
The Meiji restoration gave a great impact on Japan development into a developed nation. The development of Japan at the Meiji restoration periode required funds in great quantity. The Zaibatsu was a group of entepreneurs with a lot of funds and had developed businesses in various sectors. The cooperation between the Meiji goverment and the Zaibatsu made the restoration well-worked. This research aims to know the contribution of Zaibatsu in granting funds for the development of Japan. This research also describes the history of Zibatasu development. The result of cooperation between the Government of Meiji imperialism and the Zaibatsu was showed by the success of Japan in becoming an industrial nation by retaining its traditional nature. Beside that, the Meiji imperialism had been succeded in developing the economy of Japan. In addition, Japan also had become an imperial nation, showed by the Japanese victory over Russia for taking Korea as the market of Japan industrial products during the reign of Meiji imperialism periode. The Zaibatsu became the side that succesfully advance the economics of Japan so Japan can become a developed nation in the economy, especially in the industry. Keywords: contribution, Zaibatsu, development, Meiji, Japan